Strategi Komunikasi Guru Pembina OSIS dalam Menanamkan Sikap Nasionalisme Sebagai Benteng Radikalisme Siswa MA Al Khidmah Ngronggot - Badrus; Mohammad Auzai Aqib (Jurnal Kopis: Kajian Penelitian dan Pemikiran Komunikasi Penyiaran Islam, 2021)
The emergence of radicalism has recently become increasingly widespread, if this harsh understanding is not immediately addressed, it will endanger the life of society and the state. The development of radicalism is not easy to prevent suddenly, therefore from an early age starting at the school level, especially at the high school level, fostering an attitude of nationalism and preventing radicalism needs to be instilled. This study reveals the teacher's communication strategy in instilling the attitude of nationalism in the students of MA Al Khidmah Ngronggot. This study uses a qualitative descriptive method, with data mining methods of observation, interviews, and documentation. Meanwhile, data analysis uses the theory of Miles and Hubbeman, namely, data reduction, data display and drawing conclusions. Finally, this paper can be concluded that the strategy of the OSIS coach in instilling an attitude of nationalism through several ways, among others, is to explain knowledge properly and correctly, build an understanding of living together, and provide achievement motivation to OSIS members. These three methods are carried out by the builder teacher with full affection and attention to students. These three methods are new findings in the field to enrich communication science in building the attitude of nationalism and at the same time fortify radicalism in this country.